Ranking Cognitive–Affective Factors in the Development of Psychosomatic Illness - Mata , Giselle; Rodrigues da Silva , Diana; Peixoto, Beatriz (Journal of Personality and Psychosomatic Research (JPPR), 2026)
This study aimed to identify and rank the key cognitive–affective factors contributing to the development of psychosomatic illness through an integrated qualitative–quantitative research design. A mixed-methods sequential design was employed. In the qualitative phase, an extensive literature review of 127 scientific sources published between 2000 and 2025 was conducted to identify the principal cognitive–affective mechanisms underlying psychosomatic illness. Using NVivo 14 software, open and axial coding were applied until theoretical saturation was achieved, resulting in seven major thematic categories. In the quantitative phase, a structured questionnaire was developed based on these qualitative findings and administered to 288 adult participants from Portugal. Participants rated the importance of each factor on a 5-point Likert scale. The collected data were analyzed using SPSS version 26, with descriptive and inferential analyses determining the ranking and significance of each factor. The results showed that emotional dysregulation was the most influential factor contributing to psychosomatic illness (M = 4.62, SD = 0.43), followed by stress reactivity and coping deficits (M = 4.48, SD = 0.52) and maladaptive cognitive appraisal (M = 4.36, SD = 0.58). Relational and attachment factors ranked fourth (M = 4.27, SD = 0.61), while body–emotion misattribution and personality traits followed with moderate influence. Health beliefs and mind–body awareness received the lowest mean score (M = 3.89, SD = 0.67). Inferential analyses indicated statistically significant differences across demographic groups, with higher psychosomatic sensitivity observed among participants with greater emotional suppression and lower coping efficacy. The findings highlight emotional dysregulation and maladaptive stress processing as the most critical cognitive–affective determinants of psychosomatic illness. Interventions targeting emotion regulation, adaptive coping, and cognitive restructuring are essential to prevent and manage psychosomatic symptoms.